Ancient Landscapes of Western North America A Geologic History with Paleogeographic Maps - Blakey, Ronald C. (Springer International Publishing, 2018)
Allow yourself to be taken back into deep geologic time when strange creatures roamed the Earth and Western North America looked completely unlike the modern landscape. Volcanic islands stretched from Mexico to Alaska, most of the Pacific Rim didn't exist yet, at least not as widespread dry land; terranes drifted from across the Pacific to dock on Western Americas' shores creating mountains and more volcanic activity. Landscapes were transposed north or south by thousands of kilometers along huge fault systems. Follow these events through paleogeographic maps that look like satellite views of ancient Earth. Accompanying text takes the reader into the science behind these maps and the geologic history that they portray. The maps and text unfold the complex geologic history of the region as never seen before.